Caracterização morfológica, citogenética e molecular em cultivares de trigo - Scariot, Gabrieli (2013)
The characterization of cultivars has got great importance in recent years because of allowing its registration and protection, benefiting the breeder, seed producers and farmers. The objective of this study was to characterize the BRS 327, BRS 331, BRS 374, BRS Parrudo and BRS Guamirim cultivars regarding to morphological, cytogenetic and molecular aspects, describing the existing morphological differences between them. These studies have also aimed to analyze pollen viability and determination of genetic distance between cultivars, allowing the confirmation of stability, uniformity and intrinsic genetic differences of the materials. Wheat plants from plots of genetic seed multiplication were collected from the experimental field of Embrapa Wheat, Passo Fundo RS, in 2011 and 2012. The description of genotypes in relation to morphological characteristics was made in accordance with specific standards for the National Register of Cultivars in Brazil. It was found that the described number of spikelets per spike, number of grains per spike and tooth length of glume, recommended by the National Service for Plant Variety Protection, presented the coefficient of variation close to or above 20% which show that they are less reliable and accurate for registration and protection of plant characteristics. Regarding the cytogenetic and molecular analyzes, these were taken with a sampling from the same plants evaluated in the field in 2011. In the first case, it was analyzed the normal or feasible variables (uninucleate pollen grains of bi/trinucleate) unviable (empty) and sizes differences Uninucleate pollen ranged from 1.16 to 1.57%, Bi / trinucleate ranged from 95.8 to 98.0% and empty from 1.20 to 1.52%. The pollen grain diameter ranged from 61.77 to 53.80 micrometers. Molecular genotyping by microsatellite markers dispersed in the three genomes of wheat, allowed the determination of genetic distance between the cultivars and the dendrogram generated were evident in three different groups: BRS Parrudo and BRS 331 formed a group; BRS 327 and BRS 374 formed another group which were genetically more distant than the first, and BRS Guamirim, with greater genetic distance than the other genotypes, consisting of a third group. Therefore, this work represents a contribution to the study of morphological descriptors, in order to revise what are the most accurate to distinguish one cultivar, as well as the use of analyzes of genetic uniformity and stability for the purpose of protection of plant varieties, through analysis cytological and molecular